Using interactive storytelling approach in science education - Jamaluddin, Robiatul A'dawiah; Badioze Zaman, Halimah (2010)
This research was aimed to develop interactive multimedia software and to determine its competencies. This Computer Aided Learning (CAL) was established based on National Pre-School Curriculum, 2006, Education Ministry of Malaysia. This Computer Aided Learning (CAL) focused on Science subject with the theme of "Explore the Space" for pre-school level. The development of educational multimedia software with animated story approach making the learning process more fun as well as enable teachers to convey knowledge in easier way. Furthermore, this study refers to the learning theories, for instance, behaviorism, cognitivism, constructivism as well as scaffolding. This software package was developed using ADDIE methodology and Adobe Director 11 software as the base. The interactive animated story approach used in the exploration module includes stories of 9 planets in the solar system; Mercury, Venus, Earth, Mars, Jupiter, Saturn, Uranus, Neptune and Pluto. Early analysis was done in 10 preschools managed by the Education Ministry of Malaysia. From the analysis, it was found that the current Science teaching is teacher-oriented. This contributes to the development of the children with criterion such as passive, lack of confidence to speak and depend solely on their teachers.